Maximal strength training improves running economy in distance runners - Storen, O.; Helgerud, J.; Stoa, E. M.; Hoff, J. (Medicine & Science in Sports & Exercise, 2008)
Purpose: The present study investigated the effect of maximal strength training on running economy (RE) at 70% of maximal oxygen consumption (VO2max) and time to exhaustion at maximal aerobic speed (MAS). Responses in one repetition maximum (1RM) and rate of force development (RFD) in half-squats, maximal oxygen consumption, RE, and time to exhaustion at MAS were examined.